Effect of Board Gender, Political Connection, Military Experience, and Board Activity Toward Company Reputation - Zaenal Fanani; Linda Suci Alfiyanti (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of board gender, political connection, military experience, and board activity to the corporate reputation for the year 2014-2016. The population in this study are companies which listed in Indonesia's Top 100 Most Valuable Brand rankings from SWA magazine for the year 2014, 2015 and 2016. Purposive sampling is used to determine the sample with a total of 223 firm-year observations. Multiple linear regression analysis techniques were performed to analyze whether board gender, board activity, political connection, and military experience are associated with corporate reputation. The results show that board activity and political connection have a positive effect to the corporate reputation. Military experience has a negative effect to the corporate reputation. However, board gender does not have significant effect to the corporate reputation. This research contributes to the development of science or accounting issues by testing the political connection, military experience, and board meeting variables as independent variables and company's reputation as dependent variable, this model has never been done by researchers before.